Enhancing procurement efficiency: A business process re-engineering case in frozen food retail - Hasibuan, Rizki Prakasa; Larisang, Larisang (Journal Industrial Servicess, 2024)
Enhancing business process performance is critical for maintaining organizational competitiveness. Delays in processes often arise from the complexity of activities supporting business operations. Procurement is a key area within this context, as it plays a vital role in fulfilling operational requirements. This study focuses on analyzing the existing procurement process and evaluating the potential benefits of adopting an e-procurement system to boost efficiency. Using the Business Process Reengineering (BPR) approach, this research assesses current workflows and proposes optimized alternatives. The study outcomes include the design of a new procurement process aligned with BPR principles, aiming to minimize costs, shorten cycle times, enhance automation, and improve information accessibility and inventory management. Implementing these changes is anticipated to enhance procurement performance and operational efficiency.